Avaliação dos processos de lavagem com água e de filtração por membranas na purificação de biodiesel - Alves, Magno José (2012)
Biodiesel is a potential substitute fuel to petroleum diesel due to issues related to energy and environmental demands. One of the critical stages of the production process of biodiesel is its purification. Conventionally, biodiesel is purified by successive washes with clean water. This process uses considerable amounts of water, what results in a high volume of effluent to be treated. The aim of this research was to evaluate the process of membrane filtration as an alternative for the biodiesel purification. The first step of this work was the production of biodiesel used for further purification. This production was performed by transesterification reaction using refined soybean oil as raw material. Biodiesel was then purified by two processes: by the traditional method (successive washings with water) and by the processes using membranes. A central composite design (CCD) was performed to evaluate the volume of water used and the temperature in the biofuel purification process by the conventional method of washing with water. According to the surface response obtained, it was possible to analyze the variables effects and to determine the minimization point, which represented 64 mL of water for 100 mL of biofuel and temperature of 49.6°C. The efficiency of ultrafiltration and microfiltration membranes (polymeric and ceramic) in the biodiesel purification obtained by homogeneous catalysis via methylic route was also evaluated. Polymeric membranes of microfiltration, flat type, mixed cellulose ester with pore diameters of 0.22 and 0.30 μm, polymeric membranes of ultrafiltration, poly (ether sulfone), flat type, 10 and 30 kDa nominal MWCO and ceramic membranes of ultrafiltration, α-Al2O3/TiO2, tubular, 5 kDa. The polymeric membranes were evaluated in a module that uses the principle of perpendicular and the ceramic membrane filtration was evaluated in tangential filtration. In the process using membranes, all experiments were performed at room temperature. The microfiltration experiments were carried-out at two different transmembrane pressures, 1 and 2 bar. Experiments with ultrafiltration membranes were performed at a transmembrane pressure of of 4 bar. These pressures were chosen based on preliminary tests . The membrane performance was evaluated by the retention capacity of glycerin and by the values of permeate flows after stabilization. Besides filtrations of raw biodiesel, additional tests were performed with the addition of small amounts of water in raw biodiesel before filtration (in batch and continuous modules). These tests were performed with membranes, what showed better results in preliminary tests (polymeric of 10 kDa and ceramic of 5 kDa). Deionized water was added to the biodiesel sample in concentrations of 0,1 and 0,2% by weight. The amount of free glycerol dropped in all filtration performed. However, between the membranes discussed, the required level of free glycerin (0,02 wt%) was attained only with the 10 kDa membrane. The addition of small amounts of water significantly increased removal of glycerin and it fit the biodiesel into the legislation with regard to the content of glycerin.